Analisis Hukum Penerapan Blockchain dan Internet of Things (Iot) pada Perlindungan Data Pribadi dalam Transaksi Bisnis E-Commerce di Indonesia - Oktaviona, Bintang Sutra (Proceedings Series on Social Sciences & Humanities, 2024)
Today, e-commerce is one example of continuous development in technology and information. However, there are some problems with its implementation. One of them is a cyber security system that regulates e-commerce user data which can leak and misuse personal data. In this case of personal data leakage, increasingly advanced technological advances are clearly the cause. This causes problems in society and legal processes. Service users can sue e-commerce companies if personal data is misused. This is because users feel disadvantaged due to misuse of this data. This research uses empirical juridical as a research method, with descriptive analytical research specifications. The research results show that the world of civil law has changed privacy due to technological advances. Studies show that security threats and strategies affect the security of e-commerce users' personal data.